2005
DOI: 10.1038/ng1636
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous HOXA1 mutations disrupt human brainstem, inner ear, cardiovascular and cognitive development

Abstract: We identified homozygous truncating mutations in HOXA1 in three genetically isolated human populations. The resulting phenotype includes horizontal gaze abnormalities, deafness, facial weakness, hypoventilation, vascular malformations of the internal carotid arteries and cardiac outflow tract, mental retardation and autism spectrum disorder. This is the first report to our knowledge of viable homozygous truncating mutations in any human HOX gene and of a mendelian disorder resulting from mutations in a human H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
248
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(252 citation statements)
references
References 15 publications
1
248
0
3
Order By: Relevance
“…263,264 A HOXA1-related disorder, Bosley-Salih -Alorainy syndrome, has been identified in a small patient sample, with symptoms that include delayed maturation and autism. 265 Gene expression profiles in normal and Hoxa1 À/À embryonic stem cells have shown that Hoxa1 regulates expression of Bdnf and other genes important for development. 266 Stodgell et al 254 have shown that, in rats, prenatal exposure to valproic acid leads to marked increases in embryonic Hoxa1 expression, possibly through the inhibition of histone deacetylases.…”
Section: Mouse Models Of Environmental Contributions To Autism Etiologymentioning
confidence: 99%
“…263,264 A HOXA1-related disorder, Bosley-Salih -Alorainy syndrome, has been identified in a small patient sample, with symptoms that include delayed maturation and autism. 265 Gene expression profiles in normal and Hoxa1 À/À embryonic stem cells have shown that Hoxa1 regulates expression of Bdnf and other genes important for development. 266 Stodgell et al 254 have shown that, in rats, prenatal exposure to valproic acid leads to marked increases in embryonic Hoxa1 expression, possibly through the inhibition of histone deacetylases.…”
Section: Mouse Models Of Environmental Contributions To Autism Etiologymentioning
confidence: 99%
“…Highthroughput molecular genetics has changed the face of medical research dramatically, but it has perhaps had less of an impact on clinical medicine than one might expect [Tischfield et al, 2005]. For example, it is technically feasible to use gene-chip methodology to screen for any of several hundred possible mutations that cause cystic fibrosis [Schrijver et al, 2005].…”
Section: Clinical and Economic Aspects Of Mutation Detectionmentioning
confidence: 99%
“…В качестве примера можно привести гомозиготную мутацию в гене HOXA1, которая ассоциирована с синдромами BosleySalih-Alorainy, дискинетическим синдромом Атабаски [35]. Интересен факт, что тяжелые пороки развития сердечно-сосудистой системы (тетрада Фалло, ДАК, дефект межжелудочковой перегородки и др.)…”
Section: генетикаunclassified